Synthesis, characterization and catalytic activity of melamine immobilized MCM-41 for condensation reactions - Appaturi, Jimmy Nelson; Ramalingam, R. Jothi; Al-Lohedan, Hamad A. (Springer Verlag, 2018)
In the present study, melamine immobilized MCM-41 is synthesized by grafting on modified MCM-41. The surface area, pore size and pore volume of MCM-41-Mela were found to be decreased after immobilization of melamine. FTIR and Raman spectroscopy results revealed the successful grafting of melamine on the surface of MCM-41. The 29Si CP/MAS NMR of MCM-41-Mela showed the existence of T2, T3, Q3 and Q4 silicon centres. The catalytic activities were investigated through a liquid phase Knoevenagel condensation reaction between furfural and acetylacetone. A conversion of 93.1% was achieved with 100% selectivity towards 3-(2-furylmethylene)-2,4-pentanedione (FMP) under solvent-free condition. The catalytic activity of MCM-41-Mela was then successfully carried out for Knoevenagel condensation with different substrates, giving excellent yields of the corresponding products. The catalyst was easily regenerated and could be reused for three times without loss of catalytic activity. Simple preparation methods, high efficiency and reusability of the heterogeneous MCM-41-Mela catalyst demonstrate a great potential for future catalysis application.